2017
DOI: 10.1159/000481765
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Diameter is Inversely Associated with the Severity of Coronary Lesions in Patients Undergoing Coronary Angiography

Abstract: Background: The diameters of the coronary arteries have been suggested to be a potential predictor of coronary artery disease (CAD). However, whether the diameters of the coronary arteries are associated with the coronary lesion severity on angiography has not been determined. Methods: One hundred sixty-seven consecutive adult patients (109 men and 58 women) aged 31–84 years who underwent coronary angiography for suspected or known CAD were enrolled. The known catheter tip diameter was used as the calibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Taking into account that the coronary arteries were selected for this study, the dimensions were selected carefully from the literature to accurately mimic the real conditions of blood flow in these arteries. The diameter selection was based on real data obtained by Zhou et al [38] in 2017. Moreover, to develop the stenotic area, it was found that several authors [2], [39], [40] consider the length of the stenosis as twice the normal diameter of the artery.…”
Section: A Geometry Of the Stenotic Modelmentioning
confidence: 99%
“…Taking into account that the coronary arteries were selected for this study, the dimensions were selected carefully from the literature to accurately mimic the real conditions of blood flow in these arteries. The diameter selection was based on real data obtained by Zhou et al [38] in 2017. Moreover, to develop the stenotic area, it was found that several authors [2], [39], [40] consider the length of the stenosis as twice the normal diameter of the artery.…”
Section: A Geometry Of the Stenotic Modelmentioning
confidence: 99%
“…The diameter of the coronary arteries is strongly correlated with the risk of CHD. Zhou et al 5 evaluated the potential relationship between the coronary artery diameter and the severity of coronary artery disease. Their study involved 167 participants, including 124 patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…They compared the coronary artery diameters of the participants and found a negative correlation between the coronary artery diameter and the severity of coronary artery disease (as assessed by the Gensini score). 5 Hiteshi et al 13 found that women usually have smaller luminal diameters and therefore exhibit larger changes in the luminal area than do men with the same degree of atherosclerosis, resulting in worse prognoses for women than for men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other important point of this study was the LMCA length. Although the relationship between the coronary artery diameter and atherosclerosis is fairly well investigated (18), there is unsatisfactory data about the relationship between LMCA length and atherosclerosis. In a previous postmortem examination study, Gazetepoulos et al suggested that in patients with short LMCA the atherosclerotic lesions in the left coronary artery branches appear earlier, progress and lead more frequently to myocardial infarction, than in cases with a long left coronary artery trunk (19).…”
Section: Discussionmentioning
confidence: 99%